Optimization and validation of bioanalytical SPE - HPLC method for the simultaneous determination of carbamazepine and its main metabolite, carbamazepine-10, 11-epoxide, in plasma - Jasmina Tonic - Ribarska; Zoran Sterjev; Emilija Cvetkovska; Igor Kuzmanovski; Gordana Kiteva; Ljubica Suturkova; Suzana Trajkovic - Jolevska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
Carbamazepine is widely used as an antiepileptic drug in the treatment of partial and generalized tonic-clonic seizures. Carbamazepine 10,11-epoxide is the most important metabolite of carbamazepine, because it is a pharmacologically active compound with anticonvulsant properties. According to that, the routine analysis of carbamazepine 10,11-epoxide along with carbamazepine may provide optimal therapeutic monitoring of carbamazepine treatment. The aim of this study was to optimize and validate a simple and reliable solid - phase extraction method followed by RP-HPLC for the simultaneous determination of plasma levels of carbamazepine and carbamazepine-10,11-epoxide, in order to assure the implementation of the method for therapeutic monitoring. The extraction of the analytes from the plasma samples was performed by means of a solid-phase extraction procedure. The separation was carried out on a reversed-phase column using isocratic elution with acetonitrile and water (35:65, v/v) as a mobile phase. The temperature was 30°C and UV detection was set at 220 nm. The extraction yield values were more than 98% for all analytes, measured at four concentration levels of the linear concentration range. The method displayed excellent selectivity, sensitivity, linearity, precision and accuracy. Stability studies indicate that stock solutions and plasma samples were stabile under different storage conditions at least during the observed period. The method was successfully applied to determine the carbamazepine and carbamazepine-10,11-epoxide in plasma of epileptic patients treated with carbamazepine as monotherapy and in polytherapy. In conclusion, the proposed method is suitable for application in therapeutic drug monitoring of epileptic patients undergoing treatment with carbamazepine.